PENGARUH BAHAN AJAR KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI STKIP PGRI JOMBANG - Wahyu Anjarsari, Riski Dwi; Dinaloni, Diah (JPEAKU (Jurnal Pendidikan Ekonomi Akuntansi Kewirausahaan), 2023)
This study aims to explain the effect of entrepreneurship teaching materials on interest in entrepreneurship in students of the economic education study program STKIP PGRI Jombang. This research is a quantitative research, which uses simple linear regression analysis as its approach. The total population of the study was 114 active students of the 2018 2019 and 2020 economic education study programs. Taken using a proportional random sampling technique, 90 samples were obtained. Data was collected by means of questionnaires or questionnaires, documentation and interviews. The results showed that the results of the influence of entrepreneurship teaching materials on the interest in entrepreneurship in students of the economic education study program STKIP PGRI Jombang, evidenced by a significance value of 0.000 < 0.05